Recording the temple of Sethos I at Abydos in Egypt - Baines, J (Ancient Orient Museum, 1990)
Preliminary report on fieldwork intended to contribute to the publication of vol. V of Amice M. Calverley et al., The temple of King Sethos I at Abydos. The history of the project and methods of recording are reviewed. The areas covered by the work, which was conducted in 1979, 1981, 1983, and 1988, include the Hall of Soker and Nefertem, the Chapel of Soker, the Chapel of Nefertem, the Gallery of Lists, Corridor, and Stairway, and the Hall of Barques and Upper Gallery above. A plan, five photographs, and a reinforced photograph are included.